PROGRAM PPG UNTUK MEMBANGUN KOMPETENSI GURU GEOGRAFI (STUDI KASUS DI UNIVERSITAS NEGERI MALANG) - Mega Prani Ningsih; Achmad Fatchan; Singgih Susilo (Graduate School of Universitas Negeri Malang, 2016)
The purpose of rhe research to explain PPG SM3T Program designs for building the grogrphy teacher competences, the graduates of SM3T’s Program. The design implementation of PPG SM3T includes curriculum development process till the evaluation of geography teacher competences. Competence referred to are competence pedagogical, competence personality, social competence, and professional competency. The research is a case study researchs in Malang State University. Technique the data collection was done through in-depth interviews and documentation. Data analysis use the interactive model Miles and Huberman. This research result indicates that an implementation program PPG includes several stage are: (1) the developmental syllabus stages by the appropriate policy regarding university, (2) the pre the condition stages as the combined with plenary 1, (3) the learning system stages are consist of several stage and learning activities, thy are: (a) workshop SSP stages consist of the stage activity: plenary 2 namely the deepening of material curriculum 2013; pre-test; focus group discussion are the subject matter of geography and pedagogical that have not understood, yet; independent working group is composing device learning, combined the stage of plenary 3, revision and approval lesson plans that is peer teaching, formative tests , KKL and doing incidental activity such as writing journals and scientific paper; (b) the stage of PPL consist of procession submission the PPL students to school, KMD trainings by the PPG, doing some teaching and non teaching activities, PTK researchs, and a test of the performance by lesson study; (c) the competency test stages which are consist of intensification of the subtansial geography materials, also the local and national examination test. The implementation directed in developing geography teacher competences which are consist of pedagogik, personality, social and professional competences.Tujuan penelitian ini untuk menjelaskan bentuk implementasi Program PPG SM3T dalam membangun kompetensi guru geografi alumni program SM3T. Bentuk implementasi Program PPG SM3T meliputi proses pengembangan kurikulum hingga penilaian kompetensi guru geografi. Kompetensi yang dimaksud adalah kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial, dan kompetensi profesional. Penelitian ini merupakan penelitian studi kasus di Universitas Negeri Malang. Teknik pengumpulan data dilakukan melalui wawancara mendalam dan dokumentasi. Analisis data menggunakan model interaktif Miles dan Huberman. Hasil penelitian ini menunjukkan bahwa bentuk implementasi Program PPG meliputi beberapa tahapan, yaitu (1) tahap pengembangan silabus oleh pihak terkait sesuai kebijakan universitas; (2) tahap pra kondisi sebagai gabungan tahap pra kondisi dan pleno 1; (3) tahap sistem pembelajaran yang terdiri dari beberapa tahapan dan kegiatan pembelajaran, yaitu (a) tahap workshop SSP terdiri atas tahapan kegiatan pleno 2, yaitu pendalaman materi kurikulum 2013, pre-test, diskusi kelompok yaitu diskusi materi geografi dan pedagogik yang belum dipahami, kerja kelompok mandiri yaitu menyusun perangkat pembelajaran, gabungan tahap pleno 3, revisi dan persetujuan RPP, yaitu peer teaching, tes formatif, KKL dan melakukan kegiatan insidental seperti menulis jurnal dan artikel ilmiah; (b) tahap PPL terdiri dari tahapan prosesi penyerahan mahasiswa PPL ke sekolah, pelatihan KMD oleh pihak PPG, melakukan kegiatan mengajar dan non mengajar, penelitian PTK, dan uji kinerja berupa Lesson Study; dan (c) tahap uji kompetensi terdiri dari, pendalaman materi subtansial geografi, Ujian Tulis Lokal, dan Ujian Tulis Nasional. Tahapan implementasi diarahkan dalam membangun kompetensi guru geografi, yaitu pedagogik, kepribadian, sosial, dan profesional.